A DSL for elastic component-based cloud application. (8th November 2019) - Hiba, Saddam Hocine; Belguidoum, Meriem
The deployment of component-based applications in cloud systems environment is becoming more and more complex. It is expected to provide elasticity in order to allow a deployed application to scale dynamically and meet variation in demand while ensuring a certain level of quality of service (QoS). However, there are still some open issues associated with the elasticity management. A conceptual model of elasticity management enabling the description of deployment and application constraints, properties and elasticity strategies at different levels (depending on the internal application architecture or on the cloud infrastructure and platform) in an automatic way is needed. In this paper, we propose a domain specific language (DSL) based on a metamodel, which precisely specifies three main views: the cloud service models, the automatic elasticity management strategies and the internal cloud application architecture. We illustrate through a case study, the MAPE-K-based approach using different scenarios of automatic elasticity management.